A class Ⅲ bacteriocin with broad-spectrum antibacterial activity from Lactobacillus acidophilus NX2-6 and its preservation in milk and cheese. (March 2021) - Meng, Fanqiang; Zhu, Xiaoyu; Zhao, Haizhen; Nie, Ting; Lu, Fengxia; Lu, Zhaoxin; Lu, Yingjian
Abstract: A novel class Ⅲ bacteriocin gene ( NX371 ) was mined by bioinformatic analysis from Lactobacillus acidophilus NX2-6, which had 98.15% homology of helveticin J (GenBank: ARF21596.1 ) from Lactobacillus. helveticus R0052. Then the bacteriocin NX371 (37.1 kDa) was expressed in Escherichia coli, purified and refolded to investigate its stability and antimicrobial characteristics. It displayed dramatic antimicrobial activity against both Gram-positive and Gram-negative foodborne pathogens, including Salmonella, Yersinia, Listeria, Enterobacter, Shigella, Escherichia, Staphylococcus, and Vibrio, which killed bacteria by weakening their cell wall, increasing the permeability of the membrane, and causing leakage of intracellular ATP. Furthermore, it showed a more extensive range of pH stability (3.0–8.0) than nisin and used to control the growth of pathogens in artificially contaminated milk and Mozzarella cheese ( S. enteritidis, L. monocytogenes, E. coli, and S. aureus ) at 25 and 35 °C, respectively. The number of bacteria in milk and cheese was reduced by 3.5–4.0 CFU/mL and 5.0–7.0 log CFU/g in the presence of 2.0 MIC90 NX371, respectively. Taken together, NX371 showed a broad spectrum of antimicrobial activities with significant thermal and pH stability, suggesting that it could be applied potentially in the dairy industry to control the foodborne pathogens. Highlights: Identified a novel class Ⅲ bacteriocin with broad-spectrum antibacterial activity. Killed bacteria by weakening cell wall and increasing permeability of membrane. An extensive range of pH stability range from 3.0 to 8.0. Reduced 3.5–4.0 CFU/mL and 5.0–7.0 log CFU/g in milk and cheese, respectively.